ANALISIS RESIKO PRODUKSI DAN PERBANDINGAN PENDAPATAN USAHATANI PADI SAWAH SISTEM TANAM JAJAR LEGOWO DAN TEGEL DI DESA SUKA AGUNG KECAMATAN BUAY BAHUGA KABUPATEN WAY KANAN (JASEP, 2016)
This study aimed to analyze the production risks and to compare rice farming income with Jajar Legowo and Tegel planting system in Suka Agung Village, Buay Bahuga Subdistrict, Way Kanan District. The research location is determined by purposive. The samples taken by disproportioned stratified random sampling. The number of respondents is 30 farmers, consisting of 15 farmers who used Jajar Legowo planting system and 15 farmers using Tegel planting systems. The results showed that rice farming with Jajar Legowo planting system has the same production risks with Tegel planting systems, because it has the same coefficient of variation. On the earnings front, rice farming with Jajar Legowo planting system provides higher revenues (Rp 20.082.77,.67 per growing season) and more feasible (R / C = 3,17) than rice farming with Tegel planting systems, that provide revenue (Rp 14.447.711,34 per growing season) and R / C = 2,77.